Adequacy of the Global Financial Safety Net-Review of the Flexible Credit Line and Precautionary and Liquidity Line, and Proposals for Toolkit Reform-Revised Proposals. (Policy Papers; Policy Paper ;, 2017)
in the Fund's work stream on the Adequacy of the Global Financial Safety Net (GFSN). The paper follows the Executive Board's discussion of the Adequacy of the Global Financial Safety Net-Review of the Flexible Credit Line and Precautionary and Liquidity Line, and Proposals for Toolkit Reform on June 30, 2017 (the "June paper"),1 and presents revised reform proposals in light of Directors' views. In the absence of sufficient Executive Board support for a new liquidity facility, the paper proposes to retain the Precautionary and Liquidity Line (PLL). It also proposes to introduce a Time-Based Commitment Fee (TBCF) in light of many Directors' support for this feature. 2. This work is part of the Fund's broader work stream to strengthen the GFSN . As such, it complements the new non-financing Policy Coordination Instrument and operational principles and framework for future Fund engagement with Regional Financing Arrangements.2 3. The paper is organized as follows. Section II lays out the revised set of reform proposals. Section III sets forth issues for discussion, and proposes decisions to (i) complete the review of the Flexible Credit Line (FCL) and the PLL; and (ii) introduce a TBCF. The paper also includes an Annex that describes a planned revision to the presentation of the Fund's Forward Commitment Capacity (FCC) to provide a breakdown between precautionary and other Fund commitments.